2022
DOI: 10.3390/jof8020180
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in Growth-Promoting of Cucumber by the Endophytic Fungus Chaetomium globosum Strain ND35

Abstract: Endophytic fungi are effective in plant growth and development by secreting various kinds of plant hormones and nutrients. However, the cellular and molecular interactions between the endophytic fungi and plant growth-promoting have remained less explored. The present study was designed to explore the effects of the infection and colonization events of Chaetomium globosum strain ND35 on cucumber growth and the expression pattern of some metabolically important genes in development of the cucumber radicle. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In most studies examining the nature of symbiont genes, the expression of which is altered by the plant host, microbes are cultivated in the presence of plant extract prior to sequencing their transcriptome [ 81 , 82 , 83 ]. To simulate the microbe-plant interaction more realistically, we cultivated EC4 in the presence (and absence) of the roots from a live cranberry seedling (for the experimental set-up, see Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In most studies examining the nature of symbiont genes, the expression of which is altered by the plant host, microbes are cultivated in the presence of plant extract prior to sequencing their transcriptome [ 81 , 82 , 83 ]. To simulate the microbe-plant interaction more realistically, we cultivated EC4 in the presence (and absence) of the roots from a live cranberry seedling (for the experimental set-up, see Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the endophytic microbes reported in cucumber are: Chryseobacterium [ 20 ], Chaetomium [ 21 ], Paenibacillus [ 22 ], Paecilomyces [ 23 ], Saccharothrix [ 24 ], Aspergillus, Penicillium, Fusarium, Beauveria, Trichoderma, Colletotrichum, Cladosporium, Alternatia, Chaetomium [ 25 ], Fusarium, Chaetomium, Colletotrichum, Acrocalymma [ 26 ]. The Pencillium, Gignardia, Hypocrea, Neurospora, Eupenicillium, Lasiodiplodia observed by Abro et al [ 27 ] were found to have antagonistic activity against Fusarium oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…Chaetomiaceae synthesizes many secondary metabolites with different chemical structures and shows outstanding bioactivities [57]. Species of the Chaetomiaceae are used as biological control agents for various plant diseases, as well as as bio-organic fertilizers in crop cultivation [9,15,58]. On top of that, Chaetomium species are reported as versatile weapons against various plant pathogens and act as growth promoters in maize (Zea mays), cucumbers (Cucumis sativus), and Agaricus bisporus (edible mushroom) [9,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Species of the Chaetomiaceae are used as biological control agents for various plant diseases, as well as as bio-organic fertilizers in crop cultivation [9,15,58]. On top of that, Chaetomium species are reported as versatile weapons against various plant pathogens and act as growth promoters in maize (Zea mays), cucumbers (Cucumis sativus), and Agaricus bisporus (edible mushroom) [9,[59][60][61]. Most importantly, the species in Chaetomiaceae produce industrially relevant enzymes, significantly benefiting agriculture, biotechnology, ecosystems, food production, and human health [15,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation